AVANCES INMUNOHISTOQUÍMICOS DE LA LEISHMANIASIS TEGUMENTARIA EN CAVIDAD BUCAL - Romero R., Roberto (2000)
The purpose of this work is to determine that inadequate lipcomissural cicatrisation is in relation to despolimerization of mucopilasaccharide submucous and its interrelation with extracellulars poteins (albumins and globulins). They secrets plasmatics cellulas of the bucal mucous. With this finality it was studied 35 cases of tegumentary leishmaniasis, thus it was detected in lipcommissural region impetigo and ectimatoid ulcerous injuries in 12 cases, 34%.It was performed histopatological cuts in the inmunohistochemical study that corresponded o the lipcommissural region. It was examined that in PAS coloration the primary sustance with the glucoaminoglucans took a strong pink color because of despolimerization.Conclusion: 1. On healing the lipcommissural injuries develop fibrous scars. 2. The lipcommissural cicatrisation shows possitiveness through PAS colorants and tricomicones Masson and Malory have a fundament on despolimerization phenomenon which takes to a tisular restoration of primary substance fibrosis. 3. The lack of possitiveness with fluorchromiums are determining that in this leishmaniasic disease exist a lack o gammaglobulines also.